The Politics of Mobilizing Pro-Democracy Citizens in the Empty-Box Voting Movement in the 2024 Pangkalpinang Local Election - Novendra Hidayat; Sigit Nugroho; Herza Herza (Universitas Teuku Umar, 2026)
This article analyzes the politics of mobilizing support for the empty-box option in the 2024 Pangkalpinang local election, positioning it as a form of citizens’ electoral resistance to the narrowing of competition under single-candidate dominance. Using a descriptive qualitative approach through in-depth interviews, participant observation, and documentary analysis the study maps: (1) patterns of mobilization and volunteer networks, (2) movement resources (socio-cultural capital) and their negotiation with elite political capital, and (3) policy implications arising from regulatory gaps after an empty-box victory. The findings show that mobilization was organic and grew through cross-class community nodes (e.g., BOTAK, PKK, and Baju KOKO), supported by cultural framing, network-based communication (WhatsApp/social media), and solidarity practices that substituted for conventional political logistics. At the same time, the empty-box victory unfolded within local power relations in which political capital and kinship politics shaped the opportunity structure and narrowed formal channels of competition. The article offers recommendations to strengthen the governance of single-candidate local elections: clarifying the status and rights of the empty box in electoral regulation, strengthening internal party democracy, and developing mechanisms to prevent nomination cartelization so that electoral competition remains meaningful.